Study protocol to assess the impact of an integrated nutrition intervention on the growth and development of children under two in rural Bangladesh - Gulshan Ara; Kazi Istiaque Sanin; Mansura Khanam; Shafiqul Alam Sarker; Sihan Sadat Khan; Mahfuza Rifat; Imran Ahmed Chowdhury; Sufia Askari; Kaosar Afsana; Tahmeed Ahmed (BMC, 2019)
Abstract Background The period from birth to two years is the "critical window" for achieving optimal growth and development. An inadequate quality and quantities of complementary foods, poor child-feeding practices and infection negatively impact the growth of under-twos. Approximately one-third of under-fives in developing countries are stunted; many are also micronutrient deficient. An estimated 6% of mortalities among under-fives can be prevented by ensuring optimal complementary feeding. The objective of the study was to assess the ability of a 12-month integrated nutrition intervention to improve the nutritional status (length-for-age Z-score) of 6 to 12-month-old children in rural Bangladesh. Methods In this community-based randomized controlled trial, the intervention group received a package of interventions that includes, food vouchers; to prepare egg-based nutritious snacks (suji firni for < 1-year-olds, suji halwa for > 1-year-olds), micronutrient powder to fortify children's food at home, child feeding counselling and water, sanitation and hygiene (WASH), behaviour change communication. The control group received routine health messages provided by the government. Baseline and endline surveys were conducted; Data collection was performed monthly on children's growth, food voucher utilization, child feeding and morbidity. In addition, we assessed the cognitive development of the children after 12 months of intervention. Conclusion This trial aims to explore whether an integrated nutrition intervention can mitigate childhood stunting during the critical window of opportunity in rural Bangladesh. The results may provide robust evidence to improve the linear growth of children in developing countries. Trial registration The study was retrospectively registered on August 17, 2018 and is available online at ClinicalTrials.gov (ID: NCT02768181).